Pengembangan Sistem Monitoring Pengelolaan Tata Tertib Siswa sebagai Sarana Penunjang Layanan Bimbingan Konseling - A'yun, Ana Qurrota; Supraptono, Eko; Suryono, Suryono (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
This research aims to produce a system of Monitoring the management of the student regulations and the test disqualified. This type of research is a Research and Development (R&D) and system development model using the model of the Waterfall. The system created by using Framework CodeIgniter and Boostrap. The results showed that the system has been successfully developed to support the services of BK in managing student violations and monitor student conduct offenses. Alpha testing generally indicates the system has managed to according to its functions. Performance testing shows Time behavior has an average time of 2.3 seconds with grade 93/A, whereas Resource ulitization shows results score/grade 85/B. Testing expert system shows all aspects of a quality system indicates the category â€œvery decentâ€ with percentage Correctness 97.92%, 93.06% Reliability, 100% Integrity, and Usability 91.64%, while beta testing User Responses gets percentage, Administrator 85.33%, operators 90.67% , and Users 90.95% which shows excellent results for support services BK.